New insights on Galectin-9 expression in cancer prognosis: An updated systemic review and meta-analysis - Chun Yan So; Yusong Li; Kwan Ting Chow (PLoS ONE, 2025)
Galectin-9 (Gal-9) has gained increasing attention in recent years in the field of cancer immunology. Its interactions with various immune cell types in the tumor microenvironment influence tumor progression, making it a novel target for immunotherapy. Despite its potential as a therapeutic target, the prognostic significance of Gal-9 in tumor cells remains unclear. Conflicting data exists on its expression levels and outcomes, prompting a comprehensive review and meta-analysis to elucidate its independent prognostic role across different cancer types. This study aims to examine the varying effects of Gal-9 expression across various cancer subtypes, providing insights into its potential as a prognostic marker and highlighting its significance in the realm of cancer treatment. To assess the prognostic significance of Gal-9 expression in cancer, we conducted a comprehensive database search across PubMed, Embase, and Web of Science, incorporating studies published until December 2024, regardless of language. Using pooled hazard ratios (HRs) with 95% confidence intervals (CIs), we evaluated the role of Gal-9 expression in predicting cancer outcomes across various cancer types. Our analysis encompassed 29 studies with a total of 4,720 patients to investigate the prognostic significance of Gal-9 expression across different cancer types. The results demonstrated that elevated Gal-9 expression was significantly associated with improved overall survival (OS) in solid tumors, with a pooled hazard ratio of 0.75 (95% CI: 0.63-0.90, p =  0.002). No statistically significant correlation was observed between Gal-9 expression and cancer recurrence (HR =  0.88, 95% CI: 0.65–1.19, p =  0.42). Conversely, in hematological cancers, high Gal-9 expression correlated with more rapid disease progression, as reflected by progression-free survival (PFS) or time to treatment (TTT) (HR =  2.29, 95% CI: 1.26–4.16, p =  0.007). The subgroup analyses further revealed that higher Gal-9 expression was associated with OS in gastrointestinal and urological cancers and was linked to disease-free survival (DFS) and recurrence-free survival (RFS) in hepatobiliary and urological cancers. Our research has uncovered that Gal-9 serves as a promising prognostic indicator for solid tumors, offering valuable insights into patient outcomes. High levels of Gal-9 expression within gastrointestinal, hepatobiliary, and urological cancers have been linked to better prognoses, while its presence in hematological cancers is associated with poorer outcomes. These contrasting findings emphasize the importance of interpreting biomarkers with careful consideration to the specific context. Moreover, our study sheds light on the diverse physiological roles of intracellular and secreted Gal-9, highlighting the intricate ways in which this protein influences cancer progression.